The antibacterial mechanism of perilla rosmarinic acid. (14th September 2021) - Zhang, Jinhua; Cui, Xin; Zhang, Min; Bai, Baoqing; Yang, Yukun; Fan, Sanhong
Abstract: Rosmarinic acid (RosA) is a phenolic acid compound extracted from perilla. In this experiment, the Oxford cup method was used to verify the antibacterial activity of PerillaRosA against Escherichia coli, Staphylococcus aureus, Salmonella, and Bacillus subtilis . By polyacrylamide gel electrophoresis, the effect of RosA on bacterial nucleic acid and bacterial Na + /K + ‐ATP‐ase activity, and scanning electron microscope to exploration of its antibacterial mechanism preliminarily. The results showed that RosA had antibacterial properties against all four bacteria. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of E. coli were 0.8 and 0.9 mg/ml, respectively. The MIC and MBC of Salmonella were 0.9 and 1.0 mg/ml, respectively. The MIC and MBC of S. aureus and B. subtilis were both 1.0 and 1.1 mg/ml. RosA has the bacteriostasis function, which can destroy bacterial cells and cell proteins and inhibit the activity of Na + /K + ‐ATP‐ase in cells. Abstract : RosA is a phenolic acid compound extracted from perilla. In this experiment, the Oxford cup method was used to verify the antibacterial activity of Perilla rosmarinic acid (RosA) against Escherichia coli, Staphylococcus aureus, Salmonella, and Bacillus subtilis .